Impact of the Grain for Green program on forest cover in China. Issue 3 (3rd July 2019) - Fu, Guanlong; Uchida, Emi; Shah, Muna; Deng, Xiangzheng
ABSTRACT: China's Grain for Green (GFG) program, one of the world's largest Payments for Environmental Services programs, has been implemented for more than ten years. However, empirical evidence on its impact on increasing the forest cover is still lacking. The goal of this research is to estimate GFG's effect on the total forest cover and examine its heterogeneity across four types of forests. To do so, we utilize a rich panel of GIS data set (1988–2008) containing 409 counties in four provinces. We found a small but significant treatment impact on increasing the total forest cover as well as three out of four types of forest cover, but that the impact is not equal across the forest types. We discuss the implications of these findings in future program design.